Entrepreneurship Education of Communitiy Empowerment in Bukit Barisan Selatan National Park: A Case Study in Kubu Perahu Village West Lampung - Roni, May (Universitas Islam Negeri Raden Intan Lampung, 2018)
This study aims to find out the process and result of entrepreneurship education of community empowerment in Kubu Perahu Village. This is a kind of descriptive-qualitative research focusing on the processes described in four dimensions,namely: Access to Information, Inclusion & Participation, Accountability and LocalOrganization Capacity and the results divided into two indicators, namely: IndirectIndicator of Empowerment and Direct Indicator of Empowerment. The result of theresearch shows that the process of educational empowerment inCommunity entrepreneurship carried out by the BBSNP Center and the KubuPerahu Village community has still not yet optimal. In addition the resultsof educational empowerment of entrepreneurship in the community in Kubu PerahuVillage that have not achieved success. Community empowerment and communitywelfare are still not felt as a whole. The need for improvement of cooperationbetween the Balai Besar TNBBS and the Kubu Perahu Village Community inrelation to education empowerment community entrepreneurship is mainlyrequired. The community must also think critically, creatively and innovatively inutilizing the potencies and opportunities relatedto community entrepreneurship empowerment.